2012
DOI: 10.1145/2147783.2147785
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing and advancing research networking systems

Abstract: Science in general, and biomedical research in particular, is becoming more collaborative. As a result, collaboration with the right individuals, teams, and institutions is increasingly crucial for scientific progress. We propose Research Networking Systems (RNS) as a new type of system designed to help scientists identify and choose collaborators, and suggest a corresponding research agenda. The research agenda covers four areas: foundations, presentation, architecture, and evaluation. Foundations includes pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 99 publications
(100 reference statements)
0
19
0
Order By: Relevance
“…Various potential evaluation metrics have been proposed for RNSs, e.g., measuring an increase in the publication rate of a researcher using the system 29 . Other methods of cost‐effectiveness analysis for RNSs have been suggested whereby the cost of internal networking socials for scientific professionals is weighed against the cost of RNS development both in terms of dollars spent and publication output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various potential evaluation metrics have been proposed for RNSs, e.g., measuring an increase in the publication rate of a researcher using the system 29 . Other methods of cost‐effectiveness analysis for RNSs have been suggested whereby the cost of internal networking socials for scientific professionals is weighed against the cost of RNS development both in terms of dollars spent and publication output.…”
Section: Discussionmentioning
confidence: 99%
“…The belief is that more interdisciplinary publications from within and across institutions would indicate enhanced networking and hopefully this would also come at a reduced cost. Such methods for measuring RNSs effectiveness would require a large amount of usage data that is not available for CUSP at present 29 . The paucity of query log analyses on RNSs is due, in part, to the difficulties in capturing the data and stratifying results by user type.…”
Section: Discussionmentioning
confidence: 99%
“…Spiller, Ball, Daniel, et al (2014 describe this as 'letting go' of individual focus and ' coming together' as a team. Ultimately, collaboration is time intensive and does not just happen without effort (Yu, Lau & Lee 2012;Schleyer et al 2012;O'Connor et al 2003). As a final challenge, the research team found that the pace of change with the technology used impacted the project itself, requiring flexibility and adaption in planning cycles and from researchers, institutions, and stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…However, this challenge can be mitigated when teams develop common understandings of the research question, encourage teamwork, and manage the assignment of academic credit (O'Connor et al 2003;Massey et al 2006). As can be appreciated, this becomes labour-intensive as teams work to coordinate tasks and people, often without the benefit of face-to-face meetings (Cummings and Kiesler 2005;Katz and Martin 1997;Schleyer et al 2012;Kanfer et al 2000). These challenges can be balanced by the benefits, something that teams must find a way to achieve.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation